Affective temperament, coping styles and frontal functions among elite boxing and karate athletes - Litwic-Kaminska, K.; Brzezinska, P.; Waldzinski, T.; Durzynska, A.; Stankiewicz, B.; Bartík, P.; Kochanowicz, A.; Mieszkowski, J. (Archives of Budo, 2023)
Background and Study Aim: Despite being classified into one group of combat sports, boxing and karate are two different disciplines, differing in both the technical skills required and the psychological aspects. Taking into account the insufficient interest of researchers in this issue, the aim of this study is knowledge about the difference between elite boxing and karate athletes in terms of affective temperament, styles of coping with stress and cognitive abilities, with particular emphasis on frontal functions.